2016
DOI: 10.1073/pnas.1520756113
|View full text |Cite
|
Sign up to set email alerts
|

Modular degradable dendrimers enable small RNAs to extend survival in an aggressive liver cancer model

Abstract: RNA-based cancer therapies are hindered by the lack of delivery vehicles that avoid cancer-induced organ dysfunction, which exacerbates carrier toxicity. We address this issue by reporting modular degradable dendrimers that achieve the required combination of high potency to tumors and low hepatotoxicity to provide a pronounced survival benefit in an aggressive genetic cancer model. More than 1,500 dendrimers were synthesized using sequential, orthogonal reactions where ester degradability was systematically i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
140
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(144 citation statements)
references
References 45 publications
2
140
2
Order By: Relevance
“…The EC 50 value was approximately 0.03 mg/kg, which is competitive with other potent nanoparticles that deliver siRNA to the liver. 14,19,21,29 Control LNPs delivering siGFP did not incur FVII knockdown, suggesting that the knockdown observed was not due to LNP toxicity-related effects. Furthermore, there was no significant effect on mouse body weight, suggesting low nanoparticle toxicity (Fig.…”
Section: O I10 Lnps Effectively Silenced Factor VII In Vivomentioning
confidence: 94%
See 1 more Smart Citation
“…The EC 50 value was approximately 0.03 mg/kg, which is competitive with other potent nanoparticles that deliver siRNA to the liver. 14,19,21,29 Control LNPs delivering siGFP did not incur FVII knockdown, suggesting that the knockdown observed was not due to LNP toxicity-related effects. Furthermore, there was no significant effect on mouse body weight, suggesting low nanoparticle toxicity (Fig.…”
Section: O I10 Lnps Effectively Silenced Factor VII In Vivomentioning
confidence: 94%
“…2,14,15,20,21 Although our group and others have come to appreciate the importance of tertiary amines within intracellular delivery materials, structure function understanding generally has been limited to the alkyl-amines that are one of the two precursors to lipidoids. 5,21,28,29 The structural importance of the second precursor, the alkyl tail, has not yet been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Structure-activity analysis of a heat map showing luciferase silencing indicated that the area with lower MW (PE4K) and longer alkyl thiols (C12SH) and the area with higher MW (PE8K) and shorter alkyl thiols (C6SH and C10SH) were the most active. This suggests that, in addition to optimal cationic nature and pK a , effective siRNA delivery requires a balance between the polymer MW and hydrophobicity that relates to physical chain entanglement and intermolecular forces (23,35,39,44). The top-performing polymers show superior delivery activity over the commercial benchmark RNAiMax according to dose-response curves (SI Appendix, Fig.…”
Section: A Scalable Methods Enabled Synthesis Of Polyesters With Divermentioning
confidence: 99%
“…[9, 2831] Recently, Siegwart and coworkers utilized combinatorial synthesis to build new chemical classes of biodegradable dendrimer and polymer constructs that were incorporated as the cationic component of lipid nanoparticles. [32, 33] This combinatorial approach allowed for the rapid screening and narrowing of a large chemical space which produced lead compounds highly effective for both siRNA and miRNA delivery in vivo .…”
Section: Introductionmentioning
confidence: 99%